Some cases of robbing the papal reppresentatives along the Eastern Adriatic coast in the second half of the twelfth and during thirteenth century - Majnarić, Ivan (Acta Histriae, 2007)
In this short paper the author analyses the global papal attitude towards the piracy in the second half of the twelfth and during the thirteenth century. As a starting point for this study, the author used three cases documented in Tadija Smičiklas's source collection "Codex diplomaticus Regni Croatiae, Dalmatiae et Slavoniae", involving deviant behaviour against papal representatives along Eastern Adriatic coast. The first of them deals with the case of papal nuntius Raymund de Capella (from 1177), the second with that of papal legate, subdeacon and curial chaplain Aconzio (from the early 1220s) and the third with that of the Bishop Henry of Cephalonia (from 1273). Based on the rhetoric of the papal letters related to these cases, the relevant decrees of the Third and the Fourth Lateran Councils and relying upon the previous studies of contemporary historiography on the medieval canon law, the author tries to outline the formation and development of papal attitude towards piracy along the Eastern Adriatic coast
Keywords: 12./13.st.; history; Middle Ages; Omiš; papeštvo; piratstvo; roparski napadi; srednji vek; zgodovina